Grupo de Renovación (1942-1948). Musical Neoclassicism in Cuba. (Revista Argentina de Musicología, 2014)
The history of musical neoclassicism in Cuba can be traced to 1942, when a group of composers created the Grupo de Renovación with the intention of challenging the aesthetic preferences of an audience that cultivated music as part of Havana’s sophisticated social life. The aims and actions of the Grupo de Renovación should be understood as an intellectual stance that mirrored the musical thinking of its time. Its fundamental purpose was to insert Cuban music into the mainstream of the written tradition of Western art music. Neoclassicism, understood as a modern type of eclecticism, implies the presence of folk strands in compositions by Latin Americans that rely on the scaffoldings of Western art music genres as a principal strategy to establish difference. How do Cuban composers define neoclassicism and how does musicology reconcile national identity (Hispanicity and Afrocubanism), postcolonial and neocolonial thought, external influences, and transgression of classical paradigms?  How does the incorporation of Afrocuban sounds into classical sonata forms function in contemporary concert music?
Keywords: neoclassicism; Hispanicity; Afrocubanism; group; identity